Potensi Multi Track Diplomacy (Track 7- Agama dan Track 9 - Media) dalam Drama The Fiery Priest - Adine, Nurbani; Adiine, Nurbani; Sabiqoh, Luthfiah Farras (Universitas Komputer Indonesia, 2025)
This study analyzes the potential of Multi-Track Diplomacy in the Korean drama The Fiery Priest, focusing on track 7 (religion) and track 9 (media). The Hallyu wave is viewed not only as a cultural and entertainment phenomenon but also as an instrument of South Korea’s Soft Power. Using qualitative methods with a semiotic approach, this research interprets symbols, narratives, and representations embedded in the series. The findings indicate that The Fiery Priest reflects diplomatic dimensions through religious elements and media influence. Scenes portraying communication with the Pope and the involvement of religious leaders symbolize principles of peacebuilding and religious diplomacy, highlighting respect for religious freedom and the rule of law. These aspects demonstrate the relevance of track 7 (religion) within Multi-Track Diplomacy. In addition, the global distribution of the drama through platforms such as Netflix illustrates track 9 (media), where transnational broadcasting shapes international public opinion. The series contributes to constructing South Korea’s image as a peace-oriented country, capable of mediating conflict while presenting information about the operation of Catholic institutions within its society. Overall, the drama demonstrates significant potential as a cultural product that embodies elements of Multi-Track Diplomacy through religion and media. Keywords–Hallyu, Multi-Track Diplomacy, Soft Power, The Fiery Priest